Fashioning gothic bodies - Spooner, Catherine (Manchester Gothic (Manchester, England)., 2017)
This innovative book is the first to make an explicit link between constructions of the body in Gothic literature and film and historically specific fashion discourse, from the 1790s to the 1990s.